2000
DOI: 10.1074/jbc.275.4.2837
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cyclooxygenase-2 by Hypoxia and Peroxisome Proliferators in the Corneal Epithelium

Abstract: Hypoxic injury provokes inflammation of many tissues including the ocular surface. In rabbit corneal epithelial cells, both peroxisome proliferator-activated receptor (PPAR)-inducible cytochrome P450 4B1 and cyclooxygenase-2 (COX-2) mRNAs were increased by hypoxia. PPAR ␣ and ␤ but not ␥ mRNAs were detected in these cells. The PPAR activator, WY-14,643 increased COX-2 expression. Similarly, non-steroidal anti-inflammatory drugs with the ability to activate PPARs induced COX-2 independently of prostaglandin syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 35 publications
3
64
2
Order By: Relevance
“…Alternatively, it is possible that PPAR-␣ interacts with other inflammatory pathways (e.g., NF-B, mitogen-activated protein kinases) and that PPAR-␣ activity on ICAM-1 is indirect, particularly since the activity of the PPAR-␣ ligand required additional inflammatory stimuli (i.e., IFN-␥). Nonetheless, our data that PPAR-␣ ligand-mediated induction of proinflammatory signals (e.g., ICAM-1) are consistent with previous observations that PPAR-␣ ligands enhance cyclooxygenase 2 in colonic and corneal epithelial cells (4,5), and such observations may indicate that PPAR-␣ provides a proinflammatory signal to epithelial cells. Of note, the ␥ isoform of PPAR, which was not regulated by hypoxia (see Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Alternatively, it is possible that PPAR-␣ interacts with other inflammatory pathways (e.g., NF-B, mitogen-activated protein kinases) and that PPAR-␣ activity on ICAM-1 is indirect, particularly since the activity of the PPAR-␣ ligand required additional inflammatory stimuli (i.e., IFN-␥). Nonetheless, our data that PPAR-␣ ligand-mediated induction of proinflammatory signals (e.g., ICAM-1) are consistent with previous observations that PPAR-␣ ligands enhance cyclooxygenase 2 in colonic and corneal epithelial cells (4,5), and such observations may indicate that PPAR-␣ provides a proinflammatory signal to epithelial cells. Of note, the ␥ isoform of PPAR, which was not regulated by hypoxia (see Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have suggested that the PPAR-␣ ligands such as pirixinic acid (WY14643) may enhance proinflammatory gene expression in epithelial cells (4,5). Thus, as a functional assay for PPAR-␣ activation, we examined the induction of epithelial ICAM-1 by IFN-␥ (22,26) in the presence and absence of PPAR activators.…”
Section: Functional Loss Of Ppar-␣ In Hypoxiamentioning
confidence: 99%
“…1B and 2B). Alternatively, Flur may have a different effect on COX-2 expression in different cells since the same authors also report that Flur, like Indo, significantly increases COX-2 expression in corneal epithelial cells (33), and different culture conditions may have an effect on HASM cell PPAR expression and consequently their response to NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, induced CYP4B1 gene expression levels in PBL were closely correlated to those in the non-tumor part of the liver. CYP4B1 is induced by hypoxia, 23) and hypoxia also stimulates the synthesis of CYP-derived inflammatory eicosanoids in a rabbit corneal epithelial model. 24) These results suggest that induced CYP4B1 gene expression levels are a good index of the systemic status of metabolism and inflammation.…”
Section: Discussionmentioning
confidence: 99%